Activated macrophages promote invasion by early colorectal cancer via an interleukin 1β‐serum amyloid A1 axis. Issue 10 (12th August 2021) - Sudo, Gota; Aoki, Hironori; Yamamoto, Eiichiro; Takasawa, Akira; Niinuma, Takeshi; Yoshido, Ayano; Kitajima, Hiroshi; Yorozu, Akira; Kubo, Toshiyuki; Harada, Taku; Ishiguro, Kazuya; Kai, Masahiro; et al.
Abstract: Submucosal invasion and lymph node metastasis are important issues affecting treatment options for early colorectal cancer (CRC). In this study, we aimed to unravel the molecular mechanism underlying the invasiveness of early CRCs. We performed RNA‐sequencing (RNA‐seq) with poorly differentiated components (PORs) and their normal counterparts isolated from T1 CRC tissues and detected significant upregulation of serum amyloid A1 (SAA1) in PORs. Immunohistochemical analysis revealed that SAA1 was specifically expressed in PORs at the invasive front of T1b CRCs. Upregulation of SAA1 in CRC cells promoted cell migration and invasion. Coculture experiments using CRC cell lines and THP‐1 cells suggested that interleukin 1β (IL‐1β) produced by macrophages induces SAA1 expression in CRC cells. Induction of SAA1 and promotion of CRC cell migration and invasion by macrophages were inhibited by blocking IL‐1β. These findings were supported by immunohistochemical analysis of primary T1 CRCs showing accumulation of M1‐like/M2‐like macrophages at SAA1‐positive invasive front regions. Moreover, SAA1 produced by CRC cells stimulated upregulation of matrix metalloproteinase‐9 in macrophages. Our data suggest that tumor‐associated macrophages at the invasive front of early CRCs promote cancer cell migration and invasion through induction of SAA1 and that SAA1 may be a predictive biomarker and a useful therapeutic target. Abstract : We identified that serum amyloid A1 (SAA1) is upregulated in the poorly differentiated regions at the invasive front of T1 stage colorectal cancer (CRC). We found that tumor‐associated macrophages accumulated at the invasive front, where they stimulated SAA1 upregulation in CRC cells via interleukin 1β and promoted CRC cell migration and invasion. We also show that SAA1 secreted by CRC cells stimulates matrix metalloproteinase‐9 upregulation in macrophages at the invasive front.